Review of Factors Influencing the Competitiveness of Bumiputera Furniture Entrepreneurs in the Domestic Market - Kamaruzaman Othman; Jegatheswaran Ratnasingam; Hazirah Ab Latib; Lim Choon Liat; Kelvin Foong (BioResources)
Bumiputera furniture entrepreneurs’ share of the domestic market is about 5%. Despite incentives and assistance provided by the Government, their performance vis-à-vis the non-Bumiputera entrepreneurs still lag far behind. This review aims to shed some light for future improvement on related studies. The factors identified for review are raw material, networking, culture, product, technology, market, e-commerce, government assistance, and incentives. Lack of control of raw material and poor networking among Bumiputera entrepreneurs remain a problem, while culture plays an important role in shaping their entrepreneurship skills. Years of supplying the government contract market has led them to manufacture mostly mass-produced furniture such as kitchen cabinets, school furniture, and sofas. The use of more high-tech machinery among some entrepreneurs helps to increase their production efficiency while providing no guarantee of more sales without exploring more of the open market and taking advantage of the trend in e-commerce. While the numerous government assistance and incentives extended to Bumiputera furniture entrepreneurs have succeeded in assisting and developing some of the entrepreneurs, their performance in the domestic market still has not improved significantly.